ANALIZING FACTORS THAT INFLUENCE THE IMPLEMENTATION OF NATIONAL AGENCY OF DRUG AND FOOD CONTROL (NADFC) REGULATION OF HOW TO PRODUCE FOOD ON FOOD HOME INDUSTRY IN THE BATU CITY - Wiharningsih, Nita; Amarin yudhana; Ema Mayasari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
Food production methods are regulated in NADFC regulations, thus producing products that are safe for consumption. This regulation protects producers and consumers because the products they produce are safe and suitable for consumption. The research objective is to determine the factors that influence the implementation of NADFC regulations on how to produce food on food home industry in the Batu City. The research design is quantitative with cross sectional approach. The focus of the study is analyzing the factors that influence the NADFC implementation of regulations on the way of food production in the food home industry in the Batu City. The number of samples of 67 respondents was taken by simple random sampling technique. The results of the ordinal regression test analysis showed a p-value of 0,000 <0.005, then H1 was accepted, meaning that together with the knowledge variables of business owners, facilities and infrastructure, the amount of business capital and the number of employees affected the implementation of the BPOM Regulation on the way of food production in the food home industry. It is expected that the government will be more active in providing information about the knowledge of the regulations of the Food and Drug Supervisory Agency to food companies so that it can be implemented better.